Pendekatan Terpadu Manajemen Nutrisi pada Sistem Hidroponik untuk Meningkatkan Hasil Mentimun - Adiba Azzahra; Noerisma Addawiyah Alqadri; Nabila Intan Fadiyah; Dewi Ismul Latif; Anindya Putri Inayaah; Annisa Rezki Amanda; Aannisa Suhaila; Ihza Fadlan Izzuddin; Navez Azzam Martana; Agief Julio Pratama; M. Iqbal Nurulhaq; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (International Forum of Researchers and Lecturers, 2026)
The consistent decline in cucumber production in Indonesia indicates limitations in conventional cultivation systems, particularly due to land scarcity and inefficient resource management. This condition has encouraged the development of hydroponic systems as a more controlled and productive cultivation alternative. This study aims to critically analyze the key factors determining the success of hydroponic cucumber cultivation and to identify the most influential management aspects in improving yield. The method employed is a literature review, examining various recent studies related to hydroponic systems, nutrient management, growing media, and environmental factors. The results show that the advantages of hydroponics lie not only in land and water efficiency but also in the ability to precisely control growth variables. However, optimal productivity highly depends on the proper integration of nutrient management, particularly the regulation of pH, electrical conductivity (EC), and nutrient balance, as well as the control of environmental factors such as temperature, humidity, and light intensity. Inaccuracy in a single component can significantly reduce plant performance, even when other factors are optimal. Therefore, an integrated approach combining nutrient and environmental management simultaneously is essential to enhance hydroponic cucumber productivity. This study confirms that hydroponics has strong potential as a strategic solution to support sustainable agriculture amid land limitations in Indonesia.